Epcoritamab, a Novel, Subcutaneous CD3xCD20 Bispecific T-Cell–Engaging Antibody, in Relapsed or Refractory Large B-Cell Lymphoma: Dose Expansion in a Phase I/II Trial. Issue 12 (20th April 2023) - Thieblemont, Catherine; Phillips, Tycel; Ghesquieres, Herve; Cheah, Chan Y.; Clausen, Michael Roost; Cunningham, David; Do, Young Rok; Feldman, Tatyana; Gasiorowski, Robin; Jurczak, Wojciech; Kim, Tae Min; Lewis, David John; et al.
Abstract : PURPOSE: Epcoritamab is a subcutaneously administered CD3xCD20 T-cell–engaging, bispecific antibody that activates T cells, directing them to kill malignant CD20 + B cells. Single-agent epcoritamab previously demonstrated potent antitumor activity in dose escalation across B-cell non-Hodgkin lymphoma subtypes. PATIENTS AND METHODS: In the dose-expansion cohort of a phase I/II study (ClinicalTrials.gov identifier: NCT03625037 ), adults with relapsed or refractory CD20 + large B-cell lymphoma and at least two prior therapy lines (including anti-CD20 therapies) received subcutaneous epcoritamab in 28-day cycles (once weekly step-up doses in weeks 1-3 of cycle 1, then full doses once weekly through cycle 3, once every 2 weeks in cycles 4-9, and once every 4 weeks in cycle 10 and thereafter) until disease progression or unacceptable toxicity. The primary end point was overall response rate by the independent review committee. RESULTS: As of January 31, 2022, 157 patients were treated (median age, 64 years [range, 20‐83]; median of three [range, 2-11] prior therapy lines; primary refractory disease: 61.1%; prior chimeric antigen receptor (CAR) T-cell exposure: 38.9%). At a median follow-up of 10.7 months, the overall response rate was 63.1% (95% CI, 55.0 to 70.6) and the complete response rate was 38.9% (95% CI, 31.2 to 46.9). The median duration of response was 12.0 months (among complete responders: not reached). Overall and complete response rates were similar across key prespecified subgroups. The most common treatment-emergent adverse events were cytokine release syndrome (49.7%; grade 1 or 2: 47.1%; grade 3: 2.5%), pyrexia (23.6%), and fatigue (22.9%). Immune effector cell–associated neurotoxicity syndrome occurred in 6.4% of patients with one fatal event. CONCLUSION: Subcutaneous epcoritamab resulted in deep and durable responses and manageable safety in highly refractory patients with large B-cell lymphoma, including those with prior CAR T-cell exposure.